PELUANG DAN TANTANGAN: PENDIDIKAN ISLAM UNTUK MASA DEPAN - Wahyudi, Arif (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
In al-QurÃÂ¢n affirmed that God created humans in order to render the final destination or the results of its activities as a dedication to him. Activities are intended by God is summed up in the verses of al-QurÃÂ¢n which affirms that man is the vicegerent of Allah (khalifatullah fil `ard). In its status as vicegerent on earth cans, M. Quraish Shihab explained that the man lives in nature got the power or duty of Allah, namely prosperity or building earth in accordance with the concept defined by God. The verses mentioned above, if observed, contains the concept of the meaning of human education. Man as the Caliph of Allah given a very heavy burden. The task can be carried out properly, if people equipped with knowledge, skills and noble personality in accordance with the will of Allah. All of this can be met only through education.